The role of the board of directors in the institutional strategic process within public hospitals - NICULITA, Ana (One Health & Risk Management, 2022)
Introduction. According to the normative provisions, the Board of Directors (hereinafter the BD) is an administrative and supervisory body of public hospitals, which, in addition to other exclusive (quite limited) duties, is responsible for the examination and approval of the plans of activity of the hospital. However, just as the expressions "strategic plan" or "strategy" do not appear in this task, sometimes the involvement of the BD in the examination and approval of institutional strategic documents are omitted. Material and methods. The purpose of the study is to evaluate the experience of the BD members of the public hospitals in the North region, regarding the involvement in the institutional strategic process. They expressed their opinion on the perceived role in the process of elaboration and implementation of institutional strategies; the vision, mission and set of institutional values, strategic areas, the performance of which they monitor; communication with stakeholders in the strategic context; taking corrective action in a timely manner, etc. The strategies / strategic plans of the medical institutions included in the study were analyzed too. Results. The results of the study show that the involvement of BD members of the public hospitals in the institutional strategic process is often formal and declarative. Conclusions. The study emphasizes a superficial attitude of the BD members on the strategic process or the fact that they do not have the necessary competencies to examine the institutional strategies.